P101 'Best Foot Forward Workshops': a novel supported self-management approach for foot health. (20th April 2020) - Connett, Sue; Beevor, Colin; Ward, Sam; Wong, Ernest; Cherry, Lindsey
Abstract: Background: Rheumatic foot health challenges can be multiple and wide-ranging, leading to reduced mobility or quality of life. However, the provision of foot health services is disparate. There is a need to innovate new approaches to personalised foot health care outside of traditional clinical models of service delivery. A new healthcare model was co-designed by patients, academics and clinicians from secondary and primary care Trusts, to support self-management. Part of this model included the development of 'best foot forward' workshops. There is a need to: minimise the impact of the demonstrated gap between what service users need or want and what services are providing; reduce waiting times; empower self-management; improve MDT availability for those in need; reduce the number of appointments needed to get resolution; reduce service costs; maintain patient satisfaction. Methods: The team co-designed a series of foot health workshops, at 8-week intervals. The novel workshop design extended beyond a traditional patient education session and consisted of: 1. an education session about anatomy and physiology for the lower limb, 2. social networking time, 3. a themed education session, 4. opportunity for group discussion, 5. opportunity for individual question and answer with a health professional, 6. Access to direct request for follow-up appointment. Electronic invitations were sent to all patients registered within a single rheumatology department enrolled on the electronic notification system. Posters advertising the workshops were displayed in waiting areas. After three workshops data regarding patient attendance, satisfaction, and health service use up to four weeks after the workshop was collected. Results: Nineteen, 22 and 30 patients attended the workshops respectively. Seven people attended multiple workshops. All patients reported having an unmet foot health need and would have otherwise sought a clinical appointment. Allowing for session preparation time (approx. 3 hours per session) 20 hours of clinical time was saved; the clinical waiting list was reduced by 12 sessions (6 weeks). Three patients (4%) requested one follow-up clinical appointment immediately after the workshop. No patients requested additional appointments in the four weeks after each workshop; enabling patient led review saved 71 further appointments. Patients reported content, venue and satisfactions scores of 9.6, 8.7 and 9.6/10 respectively. Conclusion: Further research is needed to confirm that patients' needs are being fully met, in addition to enabling supported self-management and improving clinical outcomes. There is potential for these workshops to be co-ordinated and facilitated by expert patient partners. The role of group interaction as a therapeutic mechanism to aid supported self-management is worthy of further study. Best foot forward workshops could represent a viable supported self-management alternative to traditional clinical models for people with rheumatic conditions. Disclosures: S. Connett None. C. Beevor None. S. Ward None. E. Wong None. L. Cherry None.